Racial equity and the USDA’s Office of Urban Agriculture granting program and urban offices - Kristin Reynolds; Cédric Gottfried; Tamarra Thomas (Journal of Agriculture, Food Systems, and Community Development)
Urban agriculture (UA) has long been practiced in the U.S. by socially disadvantaged and low-income people for the purposes of subsistence, community and resilience. Government support for UA, however, has waxed and waned, including in city and federal policy. The 2018 farm bill established the Office of Urban Agriculture and Innovative Production (OUAIP) with the mission to encourage and promote “urban, indoor, and other emerging agricultural practices” (Agriculture Improvement Act of 2018, Title XII, Sec. 12302). The inclusion of UA in federal agriculture policy was a welcome change for many urban farmers and gardeners who had long sought recognition of urban production. Yet, historical discriminatory policies and practices on the part of the U.S. Department of Agriculture (USDA) have led some farmers and advocates to be wary of the department, and may suggest reticence to engage with USDA programs. This brief shares key findings and policy recommendations from a study that sought to understand the roll-out of the OUAIP and connected programs through a racial equity lens. We used a multimethod data collection approach that included national surveys of UA stakeholders; in-depth interviews with UA stakeholders in two case study cities, New York City and Atlanta; informational interviews with Urban Service Center (USC) Leadership in cities with urban county USDA Farm Service Agency (FSA) offices; GIS mapping of publicly accessible data; review of relevant policy documents; and participant observation, including meetings of the federal-level Urban Agriculture and Innovative Production Advisory Committee (UAIPAC). The study was supported through the Socially Disadvantaged Farmers and Ranchers Policy Research Center (The Policy Center) at Alcorn State University. In this policy brief, we introduce the urban agriculture provisions in the 2018 farm bill in the context of historical discrimination within the USDA. We then provide a short overview of our 2023–2024 study exploring the establishment and outreach of these provisions among Socially Disadvantaged Farmers and Ranchers (SDFRs) urban stakeholders followed by the key findings. We conclude with a set of policy recommendations, and reflection on how these recommendations may be relevant in 2025 and beyond.